Enhancing Rice Cultivation Efficiency in Tidal Lowland of Delta Saleh, Indonesia: Precision Farming Practices for Water Management and Soil Health Improvement - Mardiansa, Edwin; Budianta, Dedik; Sodik Imanudin, Momon (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2024)
Tidal lowland is a marginal land characterized by low pH, deficient nutrients, and salinity. Despite these challenges, El Niño phenomenon often occurs during the second planting season, resulting in long droughts. However, tidal lowland must be used for cultivation due to the need for rice and the land should be treated accurately. Therefore, this research aimed to address the issues by improving the efficiency of rice cultivation on tidal lowland through precision farming practices. A survey and land analysis were conducted in tidal lowland of B typology in Delta Saleh, Indonesia, from March 2023 to June 2023. In this precision farming practice, water management was highly prioritized, starting from tertiary channels such as optimizing sluice gate operations and monitoring water levels in channels and groundwater. Additionally, pH, CEC, and C-Organic analysis were also carried out in rice cultivation, as showed by the equation Y = 0.15 - 0.001 pH + 0.000 CEC + 0.000 C-Organic. The highest production yield was 2.05 tons/ha in P5, with the SEW-10 value during cultivation activities being 778 cm and the number of days above -10 reaching 84. Moreover, the efficiency of rice cultivation was improved through precision agricultural practices by using valve sluices and levees.